Heterogeneity in conservation of multifunctional partner enzymes with meiotic importance, CDK2 kinase and BRCA1 ubiquitin ligase - Sergey Matveevsky; Tatiana Grishaeva (PeerJ, 2021)
The evolution of proteins can be accompanied by changes not only to their amino acid sequences, but also their structural and spatial molecular organization. Comparison of the protein conservation within different taxonomic groups (multifunctional, or highly specific) allows to clarify their specificity and the direction of evolution. Two multifunctional enzymes, cyclin-dependent kinase 2 (CDK2) and BRCA1 ubiquitin ligase, that are partners in some mitotic and meiotic processes were investigated in the present work. Two research methods, bioinformatics and immunocytochemical, were combined to examine the conservation levels of the two enzymes. It has been established that CDK2 is a highly conserved protein in different taxonomic lineages of the eukaryotic tree. Immunocytochemically, a conserved CDK2 pattern was revealed in the meiotic autosomes of five rodent species and partially in domestic turkey and clawed frog. Nevertheless, variable CDK2 distribution was detected at the unsynapsed segments of the rodent X chromosomes. BRCA1 was shown to be highly conserved only within certain mammalian taxa. It was also noted that in those rodent nuclei, where BRCA1 specifically binds to antigens, asynaptic regions of sex chromosomes were positive. BRCA1 staining was not always accompanied by specific binding, and a high nonspecificity in the nucleoplasm was observed. Thus, the studies revealed different conservation of the two enzymes at the level of protein structure as well as at the level of chromosome behavior. This suggests variable rates of evolution due to both size and configuration of the protein molecules and their multifunctionality.